Arricchimento semantico del turismo alpino - Clementini, Eliseo; Bartoli, Francesco (GEOmedia, 2010)
Semantic enrichment of alpine tourism Ontological enrichment from semantic Web finds its own achievement in tourism information, mostly those related to alpine world. Moreover, information systems and trails become straightforward and user-centric when tourist doesn't need to learn concepts and meanings from maps. Broad boundaries patterns accomplish this semantic refinement in order to worth both geographic appeal and routes safety, making sense of avalanche awareness risk.